Keberlakuan Hukum Perda Kota Denpasar Nomor 1 Tahun 2015 Tentang Larangan Pembuangan Sampah ke Sungai - I Gusti Agung Ngurah Diego Arimbawa; I Gusti Bagus Suryawan; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2019)
Change to habit of people to live clean and healty is difficult, the problem of dumping garbage into rivers is indeed not an easy problem to overcome, besides cultural factors there are also religious factors for the people in Bali. The community must continue to remind them how to treat waste properly and corectly, it requires direct education from the goverment, the provision of facilities and infrastructure, and law enforcement in an effort to overcome the dumping garbage into the river. Based on this background, the formulation of the problem was found in the form of 1. How is the enactment of Denpasar city regulation number 1 of 2015 concerning the prohibition of garbage disposal into rivers? 2. What factors influence the Regional Regulation No. 1 of 2015 concerning the prohibition of garbage disposal into rivers? The reseach method used is an Empirical research type by conducting research directly into the field with a legal sociology approach which is analyzed using qualitative analysis techniques supported by primary and secondary data sources and used interview techniques, observation, inventory and location determination. Formed regulations must consider various aspects, one which is not in conflict with Pancasila as the philosophy and fondation of the state of Indonesia which reflect the value system both as a means of protecting values and as a means of a realizing public behavior and monitoring and dissemination of goverment overlap in terms of implementation. Recommendations from this paper require special goverment regulations from thr both the central and regional levels to better regulate the community in waste disposal.